2018
DOI: 10.3389/fneur.2018.01001
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome and the Neurologist: From Pathogenesis to Therapy

Abstract: Antiphospholipid syndrome (APS) is an autoimmune antibody-mediated condition characterized by thrombotic events and/or pregnancy morbidity in association with persistent positivity to antiphospholipid antibodies (aPL). The nervous system is frequently affected, as intracranial vessels are the most frequent site of arterial pathology. Over the course of years, many other neurological conditions not included in the diagnostic criteria, have been associated with APS. The pathogenic mechanisms behind the syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 168 publications
0
47
0
2
Order By: Relevance
“…The involvement of aPLs in clinically significant normal procoagulant and anticoagulant reactions and on certain cells altering the expression and secretion of various molecules are the basis for possible mechanisms. Previous studies indicated that aPLs could induce a prothrombotic state through: (a) potentiating platelet aggregation and adhesiveness through upregulation of the thromboxane A2 23 ; (b) enhancing surface expression of tissue factor expression on endothelial cells and activate the extrinsic coagulation pathway 27 ; and (c) activation of the classical complement pathway and interference with endogenous anticoagulant mechanisms. 28 To date, the conclusion about the triple positivity (LACpositive, aCL-positive, and anti-b2GP-1 positive) have the highest risk for venous thrombosis 29 are inconsistent in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of aPLs in clinically significant normal procoagulant and anticoagulant reactions and on certain cells altering the expression and secretion of various molecules are the basis for possible mechanisms. Previous studies indicated that aPLs could induce a prothrombotic state through: (a) potentiating platelet aggregation and adhesiveness through upregulation of the thromboxane A2 23 ; (b) enhancing surface expression of tissue factor expression on endothelial cells and activate the extrinsic coagulation pathway 27 ; and (c) activation of the classical complement pathway and interference with endogenous anticoagulant mechanisms. 28 To date, the conclusion about the triple positivity (LACpositive, aCL-positive, and anti-b2GP-1 positive) have the highest risk for venous thrombosis 29 are inconsistent in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…APS is an autoimmune antibody-mediated disorder marked by thrombotic events 10,11. To date, antithrombotic therapy is key in its management,10, and warfarin is regarded as the standard preventative treatment 11.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a direct autoantibody-induced aggression is supposedly pathogenic (Mizisin and Weerasuriya, 2011). Antiphospholipid antibodies are linked to severe neural lesions (Snoussi et al, 2019) and are thought to induce ischemic damage by thrombosis of vasa nervorum (Imam et al, 2019) or vasculitis (Santos et al, 2010;Fleetwood et al, 2018). Antigenic determinants of the myelin phospholipids might be targets for anticardiolipin antibodies, leading to demyelinating neuropathies, as suggested by Santos et al (Santos et al, 2010).…”
Section: Immune and Metabolic Abnormalitiesmentioning
confidence: 98%